Masturbation among sexually active young women in Croatia : Associations with religiosity and pornography use - Baćak, Valerio (Array, 2011)
The aim of this study was to examine the prevalence and correlates of masturbation among sexually active young women in Croatia. Data were collected in 2010 in a cross-sectional national probability study of youth sexuality. The analyses were based on a subsample of 416 female participants aged 18 to 25. Sixty percent of the young women reported that they masturbate. Results from multivariate logistic regression analysis indicate that the participants in the older age group (22 to 25 years old) were more likely to report masturbation (adjusted odds ratio /AOR/=1.92, p<.01, compared with their younger counterparts. Pornography use was positively associated with masturbation (AOR=5.92, p<.001), while attendance of religious services was associated with lower odds of reporting masturbation (AOR=0.42-0.41, p<.05). The findings are discussed in the context of the sociocultural constraints on female sexuality and sexual health related to self-pleasuring.